Jarcho Levin Syndrome with open neural tube defect: A case report - Ali, Md Mokarram; Kadian, Yogender Singh; Ejaz, Saima; Kadian, Arnav (Journal of Neonatal Surgery, 2024)
Background: Jarcho Levin syndrome is a rare genetic disorder characterized by spine abnormalities and the absence of ribs. It is associated with various congenital malformations and carries significant morbidity and mortality. The simultaneous presentation of this syndrome with neural tube defects is seldom encountered. Case Presentation: We report a case of a 2-day-old male who presented with a lesion on his back since birth. Clinical and radiological examinations revealed thoracolumbar meningomyelocele with the absence of upper ribs on the right side and a patent foramen ovale. Subsequently, the patient underwent surgery for meningomyelocele, while the rib anomalies were managed conservatively. Conclusion: Jarcho Levin syndrome is a rare disorder, and its association with meningomyelocele is extremely uncommon. It should be considered in the evaluation of a patient with a neural tube defect and respiratory distress.